SYNCRETISM IN FIGURATIVIZATION OF ENGLISH CLASS: A TEXTBOOK ANALYSIS - Gomes, Raquel Salcedo; Gomes, Marcelo Salcedo (Laboratório Editorial FCL-UNESP, 2013)
This article aims at researching on the effects of meaning resulting from the use of syncretic verb-visual language in a foreign language textbook distributed by the National Textbook Plan for public schools across the country. We have centralized the analysis on the roles of teacher and students figurativized in the semiotic practice of class and how it is affected by the mediatization of society. To this end, we have selected the first unit of the volume prepared for the sixth grade of elementary school, analyzing it from the notions of syncretic language by L. Hjelmslev (1975) and semiotics of practices by J. Fontanille (2005). The analysis demonstrated that the English class as a social practice is conceived as a space for interaction and presence of emerging themes in contemporary society. However, despite all this coating of freshness, it is still centered in the figures of the teacher and the textbook as subjects of knowledge, whereas the student, although respected in his knowledge and freer to make choices, is still represented as its receiver.